2019
DOI: 10.1039/c9qo00619b
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of nitriles as the nitrogen source: practical and economical construction of 4-aminopyrimidine and β-enaminonitrile skeletons

Abstract: A highly practical and economical method for the synthesis of 4-aminopyrimidines and β-enaminonitriles from mixed organonitriles is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…The bond lengths and bond angles of heterocyclic rings are comparable to those presented in the analogous compounds, 26 indicating the formation of pyrimidine cores and peripheral amidine function groups.…”
Section: Rsc Advances Papersupporting
confidence: 58%
See 1 more Smart Citation
“…The bond lengths and bond angles of heterocyclic rings are comparable to those presented in the analogous compounds, 26 indicating the formation of pyrimidine cores and peripheral amidine function groups.…”
Section: Rsc Advances Papersupporting
confidence: 58%
“…1,25 We recently reported a simple and catalyst-free method for the synthesis of b-enaminonitriles and 4-aminopyrimidines by using aliphatic nitriles as electron donors and benzonitriles as electron acceptor (Scheme 2h). 26 However, the application of aliphatic nitriles and other types of aromatic nitriles (e.g. naphthyl, pyridyl, thienyl) as electron acceptors has not been concerned.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the use of less amount of 1a, such as one equivalent or two equivalents, would decrease the yields down to 54% and 66% (entries 14-15), respectively. It has been shown that the strong base of EtONa and t BuOK et al would promote an extra transformation of phenylacetonitrile to β-enaminonitrile and/or 4-aminopyrimidine by mean of self-condensation (Zhu et al, 2019;Li et al, 2020), which would lead to the loss of the starting material of 1a unwillingly. In addition, the dioxygen atmosphere is crucial for the activation of nitromethane.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, economical and practical synthetic routes of 4-aminopyrimidines and β-enaminonitrile has immense utility in organic chemistry and pharmaceutical chemistry. The application of organonitriles as a supplemental source of nitrogen is an area of great scientific interest currently in the synthesis of 4-aminopyrimidine moieties [ 52 ].…”
Section: Synthetic Strategies Of Pyrimidinesmentioning
confidence: 99%